Reasons influencing the preference of high school seniors to go to teaching or other professions - Ladaban, Concordia (Mateo) 1925- (s.n.], 1971)
The reasons that influence the preference of high school seniors to teaching and to other professions were determined. The subjects used in this study were senior students of two public and two private high schools with two sections each in the Division of Nueva Ecija for the school year 1969-1970. The investigator made use of the decriptive method of research using the questionnaire and content analysis techniques.